2006
DOI: 10.1508/cytologia.71.213
|View full text |Cite
|
Sign up to set email alerts
|

Antimutagenic Effect of Selenium and Vitamins Against the Genotoxicity Induced by Cobalt Chloride in Mice

Abstract: SummaryThe genotoxic effects of cobalt chloride (CoCl 2 ) were studied in mice using different mutagenic end points in vivo. The possible protection provided by the antioxidant selenium and vitamins (ACE) against CoCl 2 genotoxicity was also assessed. The results indicate that CoCl 2 has genotoxic effects on mice somatic and germ cells. It induced a significant increase in the frequency of chromosomal aberrations in mouse bone-marrow and spermatocytes after single and repeated oral treatments. The induction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
1
10
0
2
Order By: Relevance
“…The effect of cobalt chloride in inducing chromosomal aberrations has been observed in mice in vivo (Palit et al, 1991), and its genotoxic activities have been tested in vivo in Drosophila melanogaster by Ogawa et al (1994) and in mice somatic and germ cells by Hassan et al (2006). In M. scutellaris, we found no changes in the number and morphology of the chromosomes after treatment with cobalt chloride, and the micronucleus assay showed that the applied concentration of cobalt chloride was not mutagenic in bees.…”
Section: Resultssupporting
confidence: 55%
“…The effect of cobalt chloride in inducing chromosomal aberrations has been observed in mice in vivo (Palit et al, 1991), and its genotoxic activities have been tested in vivo in Drosophila melanogaster by Ogawa et al (1994) and in mice somatic and germ cells by Hassan et al (2006). In M. scutellaris, we found no changes in the number and morphology of the chromosomes after treatment with cobalt chloride, and the micronucleus assay showed that the applied concentration of cobalt chloride was not mutagenic in bees.…”
Section: Resultssupporting
confidence: 55%
“…For chromosomal preparations from mouse spermatocytes, the method of Hassan et al (2006) was followed.…”
Section: Cytological Preparations Chromosomal Aberrationmentioning
confidence: 99%
“…High level of vitamin C in camel milk offered nucleophilic, anticlastogenic and antimutagenic role [60][61][62][63][64][65]. Selenium and zinc protect against the genotoxic effect of toxic compounds [66][67][68][69]. Casein and its product formed during pepsin hydrolysis protect mammalian cells against certain genotoxic compounds [70][71][72].…”
Section: Cytotoxic Effectmentioning
confidence: 99%